2014
DOI: 10.1002/pmic.201300448
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of super‐SILAC based quantitative proteomics for comparison of different acute myeloid leukemia (AML) cell lines

Abstract: As a direct consequence of the high diversity of the aggressive blood cancer acute myeloid leukemia (AML), proteomic samples from patients are strongly heterogeneous, rendering their accurate relative quantification challenging. In the present study, we investigated the benefits of using a super-SILAC mix of AML derived cell lines as internal standard (IS) for quantitative shotgun studies. The Molm-13, NB4, MV4-11, THP-1, and OCI-AML3 cell lines were selected for their complementarity with regard to clinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
(30 reference statements)
0
24
0
Order By: Relevance
“…Thus, there is a risk of losing quantification of proteins only present in the patient sample. However, in our hands, the percentage of proteins in AML patient samples that could not be quantified with a super-SILAC mix of 5 AML cell lines [40] never exceeded 2% (unpublished data). With isobaric labeling techniques targeting the N-terminus and side chain amines of peptides such as isobaric tags for relative and absolute quantification (iTRAQ) and tandem mass tag (TMT) it is possible to compare up to eight and ten samples, respectively.…”
Section: Ms-based Methodologies For the Study The Aml Proteomementioning
confidence: 89%
See 1 more Smart Citation
“…Thus, there is a risk of losing quantification of proteins only present in the patient sample. However, in our hands, the percentage of proteins in AML patient samples that could not be quantified with a super-SILAC mix of 5 AML cell lines [40] never exceeded 2% (unpublished data). With isobaric labeling techniques targeting the N-terminus and side chain amines of peptides such as isobaric tags for relative and absolute quantification (iTRAQ) and tandem mass tag (TMT) it is possible to compare up to eight and ten samples, respectively.…”
Section: Ms-based Methodologies For the Study The Aml Proteomementioning
confidence: 89%
“…Their analysis of T-ALL and AML cell lines revealed the same tendencies, and showed that AML cell lines and AML patient cells did not cluster together. Hierarchical clustering of protein expression in five AML cell lines (compared and characterized in [40]) and twenty-seven AML patient samples from unpublished shotgun proteomics data from our lab showed that 560 of the 1410 proteins quantified in all thirty-two samples were significantly differently expressed in the cell lines compared to primary cells. Proteins involved in processes such as translational initiation and elongation were higher expressed in the cell lines, while proteins involved in or part of the mitochondrion were lower expressed in the cell lines, compared to the primary patient cells.…”
Section: Sample Considerationsmentioning
confidence: 99%
“…An AML spike-in reference was generated by combining Arg6-and Lys8-labeled protein cell lysates from five heterogeneous AML-derived cell lines, according to the super-SILAC (Stable Isotope Labeling with Amino acids in Cell culture) mix approach. 29,30 The spike-in reference was added to each patient sample in an 1:2 ratio (w:w; super-SILAC mix:AML patient sample) for SILAC-based quantitation.…”
Section: Aml Super-silac MIXmentioning
confidence: 99%
“…Although the tests were carried out with label-free and stable isotope labeling with amino acids in cell culture (SILAC)-labeled AML patient samples, we will only review herein our results from the SILAC-quantified samples. We used 20 µg of AML lysate and 20 µg of super-SILAC mix [30] for each proteomic workflow. We have also included two fractionation strategies using the StageTip format and the procedures with polystyrenedivinylbenzene reversed phase sulfonate (SDB-RPS, so-called mixed mode, MM) and SCX plugs described by Kulak et al [26].…”
Section: Testing Of Standard and Novel Ms-based Proteomic And Phosmentioning
confidence: 99%